2015
DOI: 10.1002/jbmr.2538
|View full text |Cite
|
Sign up to set email alerts
|

Nf1 Haploinsufficiency Alters Myeloid Lineage Commitment and Function, Leading to Deranged Skeletal Homeostasis

Abstract: While nullizygous loss of NF1 leads to myeloid malignancies, haploinsufficient loss of NF1 (Nf1) has been shown to contribute to osteopenia and osteoporosis which occurs in approximately 50 percent of neurofibromatosis type 1 (NF1) patients. Bone marrow mononuclear cells of haploinsufficient NF1 patients and Nf1+/- mice exhibit increased osteoclastogenesis and accelerated bone turnover, however the culprit hematopoietic lineages responsible for perpetuating these osteolytic manifestations have yet to be elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Low bone mineral density was reported in NF1 [Brunetti‐Pierri et al, ; Dulai et al, ; Stevenson et al, ; Yilmaz et al, ; Armstrong et al, ]. Moreover, recent studies demonstrated in vitro bone cell anomalies consisting in increased proliferation, decreased osteoblasts differentiation, and excessive osteoclasts resorption activity in Nf1 +/− mices; NF1 haploinsufficiency determines the hyperactivation of the Ras/MAPK signaling cascade, also observed in the gain‐of‐function mutations of the other Rasopathies [Alanne et al, ; Heervä et al, ; Sharma et al, ; Rhodes et al, ]. High levels of urinary resorption markers were found in patients with Ras/MAPK disorders consistent with increased osteoclast activity [Stevenson et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low bone mineral density was reported in NF1 [Brunetti‐Pierri et al, ; Dulai et al, ; Stevenson et al, ; Yilmaz et al, ; Armstrong et al, ]. Moreover, recent studies demonstrated in vitro bone cell anomalies consisting in increased proliferation, decreased osteoblasts differentiation, and excessive osteoclasts resorption activity in Nf1 +/− mices; NF1 haploinsufficiency determines the hyperactivation of the Ras/MAPK signaling cascade, also observed in the gain‐of‐function mutations of the other Rasopathies [Alanne et al, ; Heervä et al, ; Sharma et al, ; Rhodes et al, ]. High levels of urinary resorption markers were found in patients with Ras/MAPK disorders consistent with increased osteoclast activity [Stevenson et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, numerous studies explored the effects of the Ras/MAPK pathway deregulation on the skeletal development and bone metabolism [Yu et al, ; Stevenson et al, ; Stevenson and Yang, ; Choudhry et al, ; Petramala et al, ; Rhodes et al, ]. Low bone mineral density was reported in NF1 [Brunetti‐Pierri et al, ; Dulai et al, ; Stevenson et al, ; Yilmaz et al, ; Armstrong et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometric analyses on bone marrow derived macrophages (CD11b + ) from heterozygous Tet2:nGFP knock-in mice [11] revealed that all macrophages expressed high level of GFP reporter, which correlates with Tet2 protein level ( Figure 1 B). We then examined the effects of Tet2 loss on osteoclast differentiation in vitro after the stimulation of macrophages with receptor activator for nuclear factor κ B ligand (RANKL) and macrophage colony-stimulating factor (M-CSF) and counted the tartrate-resistant acid phosphatase (TRACP) positive multinucleated osteoclasts [21] . Surprisingly, the Tet2 −/− macrophage cultures contained significantly lower number of TRACP + multinucleated osteoclasts compared to WT macrophage cultures ( P < 0.001, Student’s t test) ( Figure 1 C and D).…”
Section: Resultsmentioning
confidence: 99%
“…MEL cells were maintained in RPMI1640 supplemented with l-glutamine, 10% FBS, and 1% penicillin–streptomycin. Murine macrophages and osteoclasts were obtained from in vitro culture of bone marrow mononuclear cells (BMMNCs) as described previously [21] . To generate macrophages, BMMNCs were cultured in alpha minimum essential medium (α-MEM) supplemented with 10% FBS and macrophage colony-stimulating factor (M-CSF; 20 ng/ml, PeproTech, Rocky Hill, NJ) for 3 days.…”
Section: Methodsmentioning
confidence: 99%